1998
DOI: 10.1086/301710
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Control-Region Sequence Variation in Aboriginal Australians

Abstract: The mitochondrial D-loop hypervariable segment 1 (mt HVS1) between nucleotides 15997 and 16377 has been examined in aboriginal Australian people from the Darling River region of New South Wales (riverine) and from Yuendumu in central Australia (desert). Forty-seven unique HVS1 types were identified, varying at 49 nucleotide positions. Pairwise analysis by calculation of BEPPI (between population proportion index) reveals statistically significant structure in the populations, although some identical HVS1 types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…This is consistent with analyses that previously reported on diversity in the mitochondrial D-loop of Australian Aborigine and New Guinea highland populations. A study of HVS1 found that Australian Aborigines from a riverine population tend to have higher MPSD than that of the African !Kung population (van Holst Pellekaan et al 1998). Another analysis of mitochondrial D-loop sequences also reported high nucleotide diversity in Australia, but lower than the values found in Asian and New Guinea highland populations (Redd and Stoneking 1999).…”
Section: Discussion High Mitochondrial Genome Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with analyses that previously reported on diversity in the mitochondrial D-loop of Australian Aborigine and New Guinea highland populations. A study of HVS1 found that Australian Aborigines from a riverine population tend to have higher MPSD than that of the African !Kung population (van Holst Pellekaan et al 1998). Another analysis of mitochondrial D-loop sequences also reported high nucleotide diversity in Australia, but lower than the values found in Asian and New Guinea highland populations (Redd and Stoneking 1999).…”
Section: Discussion High Mitochondrial Genome Diversitymentioning
confidence: 99%
“…Through the re-dating of the Lake Mungo skeletal remains (Thorne et al 1999;Bowler et al 2003) and as a result of several other studies (Roberts et al 1990(Roberts et al , 1994(Roberts et al , 2001), a date of 40,000-60,000 years ago is now generally accepted. The only estimate of a genetic coalescent for Australian Aborigines with individuals from outside Australia is based on mitochondrial HVS1 sequences and ranges from 60,000-119,000 years ago, depending on which substitution rate is used (van Holst Pellekaan et al 1998). In addition, an expansion date of 51,000-85,000 years ago for Australian Aborigines was estimated from mitochondrial D-loop sequences (Redd and Stoneking 1999).…”
mentioning
confidence: 99%
“…As before (Harvati and Weaver, 2006), the geographic distance between the matched genetic and morphological samples was greatest in two cases: the Australian morphological sample was not represented in the genetic data set and was coupled with a sample from Papua, New Guinea, which is geographically the closest group included in the genetic data set. Australian and Papuan New Guinea populations are thought to share a common origin and to be genetically similar (van Holst Pellekaan et al, 1998;Kayser et al, 2001). The Greenland Inugsuk morphological sample was matched with a Siberian population.…”
Section: Methodsmentioning
confidence: 99%
“…1 (4,21,(23)(24)(25)(26)(27)29) and has so far not been detected elsewhere in the world, based on the available global mtDNA database of Ͼ40,000 sequences (49). This branch is distinguished from the root of macrohaplogroup N by a transition at nucleotide position 8404.…”
Section: Australian and Ng Foundermentioning
confidence: 99%
“…1 (4,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)], we can now attempt to clarify some of the salient features of the record of Australian population history and confirm its considerable isolation.…”
mentioning
confidence: 96%